Unveiling awareness: exploring antibiotic hypersensitivity among International Islamic University Malaysia (IIUM) undergraduates in Kuantan, Pahang - Sepian, Suhada; Ruslan, Rusila (IIUM Press, 2024)
Background: The condition known as antibiotic hypersensitivity, or antibiotic allergy, poses serious problems for the medical field. Despite its importance, little is known about the awareness of antibiotic hypersensitivity, particularly among undergraduate students in Malaysia. The purpose of this study is to assess the awareness of antibiotic hypersensitivity among IIUM Kuantan undergraduate students to improve drug allergy education and healthcare practices. Methods: A general qualitative design was used to conduct the study. Semi-structured interviews were used to gather information about the awareness of antibiotic hypersensitivity. Due to their similar prevalence of antibiotic hypersensitivity, medical students served as a representative sample of Malaysia's adult population among undergraduate students from a variety of faculties. Thematic analysis was used to analyse the data. Results: Six people in all were enlisted to take part in the study. Most of the participants were female Malay students at International Islamic University Malaysia (IIUM) Kuantan Campus, Pahang, Malaysia. Two primary themes emerged from the study: (1) Antibiotic hypersensitivity awareness and (2) Factors contributing to antibiotic hypersensitivity. This finding indicated that students' knowledge of antibiotic hypersensitivity is still lacking. Conclusion: The research found evidence to suggest that additional intervention is necessary to raise awareness within the current community. Putting skill training into practice could be a good way to raise students' awareness in this area. On the other hand, more information is needed to determine the precise kind of skill training that Malaysia should adopt.